Impact of Green Accounting on Company Value: Evidence from the Nigerian Companies - Adamu Pantamee Abdurrahman (LifeSciFi, 2019)
This paper is to determine the impact of green accounting on company value in case of Nigerian Companies. The researcher opted for quantitative method of research design and collected primary data. The researcher had used Smart PLS for obtaining the data results. The analysis technique used was Confirmatory factor analysis, Discriminant validity and Path assessment. Survey questionnaire was used to collect the data. Large sample size as used to obtain accurate results. Findings revealed that the P values of all 5 hypothesis were less than 0.05 which means that there is significant relation between all the variables. Limitations are geographical area that is restricted, the sample size and the number of variables